The lead-lag relationship between oil futures and spot prices: A literature review - Miroslava Zavadska; Lucía Morales; Joseph Coughlan (International Journal of Financial Studies, 2018)
Crude oil is the dominant energy resource worldwide. The focus of this paper is on its historical behaviour and subsequent implications for the global economy with an emphasis on the lead-lag relationship between spot and future prices. The paper examines the behaviour of oil spot and future prices and their determinants during periods of market uncertainty, particularly in the context of economic and financial crises. The analysis highlights a key controversy within the extant literature, as to whether spot or futures prices are the main crude oil price indicator. The literature review indicates that the lead-lag relationship is a dynamic one, especially during periods of sustained uncertainty, which leads to significant disagreements and incongruities among researchers regarding the price that plays a dominant role.
Keywords: G01; Q40; 330; energy; crude oil; lead lag relationship; crises; literature review